2, 4-Di-tert-butylphenol, the bioactive compound produced by Streptomyces sp. KB1 - Kittisak Chawawisit , , Phuangthip Bhoopong, Worrapong Phupong , , Monthon Lertcanawanichakul , (Journal of Applied Pharmaceutical Science, 2015)
Streptomyces sp. KB1(TISTR 2304), identified by 16S rDNA gene, was collected from the air sample at Ao-nang, Krabi province, Thailand and deposited in the GeneBank database (accession number KF939581.1). It could produce bioactive compounds and excrete into liquid culture medium within 4 days of incubation period at 30 °C, 200 rounds per minute in shaking incubator. Bioactive compounds in culture broth supernatant were extracted with 3-times of ethyl acetate (EA), evaporated by rotary evaporator at 45 °C under reduced pressure, purified by silica gel column chromatography and eluted by gradient solvent system of ethyl acetate: hexane at ratio of 1:9, 3:7, 4:6, 6:4 and 10:0, v/v. Eight pooled fractions were obtained, name PF1 - PF8, from basis of their TLC profile. Only PF4 displayed as purified active compound which showed anti-methicillin resistant Staphylococcus aureus (MRSA) activity. The PF4 was predicted as 2, 4-Di-tert-butylphenol (C14H22O) with molecular weight 206.2.
Keywords: Streptomyces sp. KB1, Anti-methicillin resistant Staphylococcus aureus activity, 2, 4-Di-tert-butylphenol.